La influencia de la cinematografía en la formación profesional de los estudiantes de comunicación social de la Universidad Técnica de Babahoyo - Hervas Tamayo, Franklin Colon (2016)
This research project includes a significant and contextualized work of the importance of the influence of cinematography in the training of social communicator ECSO, with the clear objective to know the role and benefits of the cinema in the journalistic world of century XXI. To carry out this present study survey was conducted to teachers, students and graduates of the School of Social Communication at the Technical University of Babahoyo, with the goal of meeting and highlight the importance of film in journalism training, achieving obtain results They show that the vast majority of respondents know the importance of cinematography in the communications world. On the other hand, also for a more relevant research on the subject, interviews were conducted three recognized professional filmmakers of Ecuador with a long history and experience in the film area. Finally, it is proposed that initiatives such as film festivals, courses projects seeking to promote the film and audiovisual production and audiovisual experience and technique in the social communicator believe.